Pengaruh Luas Lahan, Modal dan Jumlah Produksi Terhadap Pendapatan Petani Sayur di Kecamatan Baturiti - I Gusti Ayu Bintang Pradnyawati; Wayan Cipta (Ekuitas: Jurnal Pendidikan Ekonomi, 2021)
This research aimed examine the impact of land area, capital and the total of production on the income of vegetable farmers in Baturiti District. The population in this study is all farmers who have a vegetable farming business in Baturiti District. Researchers took samples from four villages, the majority of which are vegetable farmers, namely Candikuning Village, Batunya Village, Bangli Village and Baturiti Village. The data collectied by questions given to vegetable farmers, and its analysised by multiple linear regression analysis. The results showed that (1) there was a significant simultaneous effect between land area, capital and the total production on income, (2) there was a positive and partially significant effect between land area, capital and the total of production on income. This study shows the contribution of the variable land area, capital and total production to income amounted to 44.2%, while the remaining 55.8% is influenced by other variables not examined in this study.